Identification of Potential Modulators of the RGS7/Gβ5/R7BP Complex. (October 2021) - Stoveken, Hannah M.; Fernandez-Vega, Virneliz; Muntean, Brian S.; Patil, Dipak N.; Shumate, Justin; Bannister, Thomas D.; Scampavia, Louis; Spicer, Timothy P.; Martemyanov, Kirill A.
Regulators of G protein signaling (RGS) proteins serve as critical regulatory nodes to limit the lifetime and extent of signaling via G protein–coupled receptors (GPCRs). Previously, approaches to pharmacologically inhibit RGS activity have mostly focused on the inhibition of GTPase activity by interrupting the interaction of RGS proteins with the G proteins they regulate. However, several RGS proteins are also regulated by association with binding partners. A notable example is the mammalian RGS7 protein, which has prominent roles in metabolic control, vision, reward, and actions of opioid analgesics. In vivo, RGS7 exists in complex with the binding partners type 5 G protein β subunit (Gβ5) and R7 binding protein (R7BP), which control its stability and activity, respectively. Targeting the whole RGS7/Gβ5/R7BP protein complex affords the opportunity to allosterically tune opioid receptor signaling following opioid engagement while potentially bypassing undesirable side effects. Hence, we implemented a novel strategy to pharmacologically target the interaction between RGS7/Gβ5 and R7BP. To do so, we searched for protein complex inhibitors using a time-resolved fluorescence resonance energy transfer (FRET)–based high-throughput screening (HTS) assay that measures compound-mediated alterations in the FRET signal between RGS7/Gβ5 and R7BP. We performed two HTS campaigns, each screening 100, 000 compounds from the Scripps Drug Discovery Library (SDDL). Each screen yielded more than 100 inhibitors, which will be described herein.